Bekostning ved et Drainanlæg paa Lyngbygaard ved Aarhus paa 30 Tønder Land, udført 1856. - Friis, Joh. (Tidsskrift for Landøkonomi, 2018)
Bekostning ved et Drainanlæg paa Lyngbygaard ved Aarhus paa 30 Tønder Land, udført 1856.